The Psychology of Becoming a Successful Worker Research on the changing nature of achievement at work - Määttä, Kaarina (Taylor & Francis, 2015)
In this book, we introduce our research on success at work in a very broad sense. This research can be said to have begun during the fi rst years of this millennium. Adjunct Professor Uusiautti fi rst focused on work drive in nurses and midwives, expanding her analysis to Finnish Employees of the Year, while Professor Määttä conducted her studies on love and human relationships. When our specifi c research streams converged, we began studying positive development in childhood and adolescence as well as in adulthood and later life. We even managed to incorporate our ideas on leadership. Now, we think it is time to compile our fi ndings into a psychology of success. In many parts of this book, we will refer to the route to success - we hope that this book will function as a signpost showing the way to happiness-promoting success at work. The standpoint in this book rests on psychology, particularly positive psychology. This means that we deliberately aimed to combine the themes of work success with fl ourishing and favourable development. Our purpose is to inspire and challenge researchers and all those interested to examine the possibilities of this positive approach and to consider this as one example of how to seize phenomena that are diffi cult to defi ne comprehensively but, fi rst and foremost, we want them to see the connection between success and happiness.